2*3*4 = 24
You need values for a and b, then you multiply a by 3, b by 2 and add your answers.
i need help
b2 - 7b - 6b = -4(-4)2 - 7(-4) - 6 = 16 +28 - 6 = 38
b-4 expression example b = 10 so b-4 = 6
By following BODMAS, evaluate the inner brackets first, collecting terms together as you go: B - 3(B - 4(1 - B)) = 54 → B - 3(B - 4 + 4B) = 54 → B -3(5B - 4) = 54 → B - 15B + 12 = 54 → -14B = 42 → 14B = -42 → B = -3 Check by substituting back into the original equation: B - 3(B - 4(1 - B)) → -3 - 3(-3 - 4(1 - -3)) → -3 - 3(-3 - 4(4)) → -3 - 3(-3 - 16) → -3 - 3(-19) → -3 + 57 → 54 as required.
There is nothing to "solve". You can evaluate the expression when each of a, b and c are TRUE or FALSE. But that is not solving.
The answer to the product of a and b divided by an expression that is 3 times their difference is 3ab(a+b).
3+2*A+B*4/2-4 = 3 + 2A + 2B - 4 = 2A + 2B - 1
Evaluate -4(a+b) - 10a/b when a=8 and b=5
To evaluate an algebraic expression means to simplify the expression as much as possible by replacing the variables in an expression with the numerical values given to you.Ex:Example of Evaluating an Algebraic ExpressionTo evaluate the algebraic expression '4.5 + x' for x = 3.2, we need to replace x with 3.2 and then add. 4.5 + x = 4.5 + 3.2=7.7Solved Example on Evaluating an Algebraic ExpressionEvaluate the algebraic expression p + 3q + 2p - 3q, for p = 2 and q = - 5.Choices:A. 12B. 18C. 3D. 6Correct Answer: DSolution:Step 1: p + 3q + 2p - 3q [Original expression.]Step 2: = (p + 2p) + (3q - 3q) [Group the like terms together.]Step 3: = 3p [Solve within the grouping symbols.]Step 4: = 3 x 2 [Substitute 2 for p.]Step 5: = 6 [Multiply.]
This expression is an example of the Distributive Property. The expression a(b+c) = ab +ac is true because of the Distributive Property.
Like this . . .B - 4 = 35and it is then an equation, not an expression.
A variable is a letter that represents a number. An expression that contains at least one variable is called variable expression, also called algebraic expression. A variable expression has one or more terms. A term is a number, a variable, or a product of numbers and variables. For example,3(x^2)y + 2xy + x - 7 is a variable expression, where you have 4 terms.When working with variable expression, you often use the substitution principle:If a = b, then a may be replaced by b in any expression.The set of numbers that a variable may be represent is called replacement set, or domain, of the variable. To evaluate a variable expression, you replace each variable with one of its values and simplify the numerical expression that results.Example: Evaluate the expression 2x - 4y for x = 5 and y = -9.Solution:2x - 4y= 2(5) - 4(-9)= 10 + 36=46
-1ab^2 + 5b + 8 Step-by-step explanation: 3a^2+9ab+5-4a^2-4ab+3 3a^2-4ab^2=-1ab^2 9ab-4ab=5ab 5+3=8 -1ab^2+5ab+8
It is an algebraic expression in the form of: b+14
In simple, For operators, associativity means that when the same operator appears in a row, then to which direction the evaluation binds to. In the following, let Q be the operator a Q b Q c If Q is left associative, then it evaluates as (a Q b) Q c And if it is right associative, then it evaluates as a Q (b Q c) It's important, since it changes the meaning of an expression. Consider the division operator with integer arithmetic, which is left associative 4 / 2 / 3 <=> (4 / 2) / 3 <=> 2 / 3 = 0 If it were right associative, it would evaluate to an undefined expression, since you would divide by zero 4 / 2 / 3 <=> 4 / (2 / 3) <=> 4 / 0 = undefined
It could be a^3 + b or (a + b)^3, depending on the context.
That factors to 4(a - b)(a + 3b)
9aaaabbbb = 9 a^4 b^4
The algebraic expression is 3(b+5).
Definition of Radical ExpressionA radical expression is an expression containing a square root.Examples of Radical Expressionare examples of radical expression.More about Radical ExpressionRadical: Thesymbol that is used to denote square root or nth roots.Radicand: Radicand is a number or expression inside the radical symbol.For example, 5 is the radicand in.Radical equation: An equation containing radical expressions with variables in the radicands.Radical inequality: An inequality containing a radical expression with the variable in the radicand.Solved Example on Radical ExpressionEvaluate the radical expression when a = 2 and b = 4.Choices:A. 9B. 8C. 7D. 6Correct Answer: DSolution:Step 1: [Substitute the values of a and b in the given radical expression.]Step 2: [Find the positive square root.]Step 3: [Multiply.]Step 4: [Add.]Step 5: = 6 [Simplify.]
a + b + 4 is in its simplest form.
4b - 3